Numismatic Finds from Roman Residential Object in Caska (Cadastral Plot 1941/24) (Archaeologia Adriatica, 2009)
Northern part of the island of Pag has been a challenge for archaeological science as several important and rich sites are situated in this region. One of them is about 3 km east of Novalja, in the Bay of Caska. In the last ten years in the series of archaeological explorations significant remains of Roman settlement and necropolis were discovered. Abundant numismatic material was found in these excavations, among other finds. On this occasion I would like to present Roman coins which were unearthed in 2005 and 2006 during archaeological excavations on the plot of Juraj Palčić (cadastral plot 1941/24) in Caska where remains of a complex Roman residential object were explored under the leadership of Goran Skelac. Thirteen pieces of the Roman currency were discovered in trenches. A half of a split coin probably belongs to the period of the Roman Republic (cat. no. 1). Due to poor state of preservation it cannot be dated with certainty. A well preserved bronze coin belongs to the final period of the Roman Republic (cat. no. 2). Two busts are depicted on its front side: Caesar with a wreath on his head and bare-headed Octavian. This dupondius was made in the Lugdunum (Lyon) mint. To my best knowledge, this Gallic provincial coin from approximately 36 BC is the first such find from the territory of ancient Liburnia. Then, there was also an August's as from the mint in Rome (cat. no. 3). Sex. Nonius Quinctilianus, a monetary official from the year 6 BC is mentioned in the legend at the reverse. As with a depiction of the first Roman emperor and mention of C. Marcius Censorinus was also discovered at this site in Caska (cat. no. 4). Since Censorinus was a monetary official in 18 BC who supervised minting of sesterces and dupondii only, according to the standard catalogue Roman Imperial Coinage, as with his name is probably an early imperial forgery. Following numismatic finds belong to the beginning of the second half of the 3rd century: two antoniniani from the mint in Rome with depictions of the Emperor Gallienus (cat. no. 5) and his wife Salonina (cat. no. 6). Seven coins belong to the Late Antiquity. One of them is from the period of Constantine the Great (cat. no. 7). Coin with a depiction of Caesar Constantine II, his son, is dated to the last two years of his father's reign (cat. no. 9). A coin with posthumous depiction of Constantine the Great belongs to the first decade of independent reign of his sons (cat. no. 8). Four coins belong to the period around mid-fourth century. One of them was minted in Siscia, under the Emperor Constans. Phoenix, a firebird symbolizing immortality i.e. resurrection is on the reverse (cat. no. 10). The last three coins were minted during the Emperor Constantius II. A distinctly military theme is depicted on their reverses: a Roman soldier strikes enemy on a horse with a spear (cat. no. 11-13). As a whole this numismatic assemblage contributes to a more precise chronological determination of this complex Roman residential object in Caska. It is also important for better understanding of money circulation in the region of ancient Liburnia. I would like to dedicate this article with best wishes to a dear friend and colleague, Professor Janko Belošević.
Keywords: Caska; island of Pag; ancient numismatics; Roman republican coins; Roman imperial coins; irregular ancient coins